Gender, athletes rights, and the court of arbitration for sport - Lenskyj, Helen (Bingley, U.K. : Emerald Publishing Limited, 2018)
Disputes over gender, doping, and eligibility in Olympic sport are widely covered in sport studies and in the mainstream media. Less well known are the functions of the Court of Arbitration for Sport (CAS), and the threat it poses to athletes' rights by depriving them of access to their own countries' court systems. CAS is a quasi-court that loosely follows the model of international arbitration tribunals. As in forced arbitration outside of sport, employees - in this case, high performance athletes - sign contracts agreeing to arbitration rather than litigation as the sole means of dispute resolution. Promoting the concept of sport exceptionalism, the International Olympic Committee (IOC) justifies the power it exercises through CAS by claiming that sport must be self-regulating, with disputes settled by specialist arbitrators. These arguments point to lex sportiva (global sports law) as a valid legal principle in sport-related disputes, which, it is claimed, cannot be understood or resolved by non-specialists. Self-regulation works effectively to protect the Olympic industry brand by keeping disputes 'in the family'.This critical analysis of CAS history and functions demonstrates how athletes' rights are threatened by the forced arbitration process at CAS. In particular, CAS decisions involving female and gender-variant athletes, and racialized sportsmen and women, reflect numerous injustices. As well as the chronic problem of CAS's lack of independence, other issues examined here include confidential proceedings, lex sportiva, the non-precedential system, the closed list of specialist arbitrators, and, in doping cases, the burden of proof question.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Court of Arbitration for Sport; Court of Arbitration for Sport. -- Ad Hoc Division; Sports -- Law and legislation; Law, Sports; Licensing, gaming & club law